Correlations of nasal responses to leukotriene D4 and histamine nasal provocation with quality of life in allergic rhinitis - Zhu, Zheng (Asia Pac Allergy, 2016)
BACKGROUND: The symptoms of allergic rhinitis (AR) greatly affect the quality of life (QoL) in the patients with AR. The correlations of nasal response to leukotriene D4 (LTD4) and histamine nasal provocation with health related QoL in AR are not clear. OBJECTIVE: To evaluate the correlations of nasal response to LTD4 and histamine nasal challenge with QoL in AR. METHODS: Patients randomly underwent LTD4 and histamine nasal challenge tests, completed the rhinoconjunctivitis quality of life questionnaire (RQoLQ), and rating the symptom severity score (total symptom score 4, TSS4) in the previous week. The correlations between nasal challenge tests induced nasal responses and QoL in RQoLQ were analyzed. RESULTS: A total of 25 eligible AR patients enrolled and finished both LTD4 and histamine nasal challenge and completed the questionnaire of RQoLQ. Histamine nasal challenge induced sneezing, increased nasal resistant were correlated with most of the dimensions (general, practical, nasal, eye problems, and quality of sleep, p < 0.05), while LTD4 nasal challenge induced sneeze, increased nasal resistant only correlated with nasal and ocular problems. On the contrary, the severity of the sneeze assessed by TSS4, was not correlated with QoL, while the severity of rhinorrhea, congestion, and nasal pruritus were correlated with nasal and practical problems, and nasal congestion was also correlated with ocular problems (r = 0.60, p = 0.01). CONCLUSION: LTD4 and histamine nasal challenge induced nasal responses were correlated with different clinical symptoms severity and QoL, which can be used as a good diagnosis and evaluation methods for the management of AR.